RESEARCH ON THE TRAINING MODE OF PRODUCTION EDUCATION COMBINATION OF SPORTS APPLIED TALENTS FROM THE PERSPECTIVE OF EMOTION REGULATION - Sun, Yan; Kim, San (The international journal of neuropsychopharmacology, 2022)
Abstract Background Health refers to one's complete physical and psychological state and social adaptability, not physical obstacles. Physical and mental health refers to having a healthy body and a happy state of mind. Relevant studies have proved that there is a very close relationship between human physiology and psychology. Some physiological changes or diseases will have a significant impact on people's psychological activities. The psychological state has an important influence on people's health. This paper establishes the “overall health view” centered on “sports to promote physical and mental health”, so as to comprehensively promote the physical health of the masses. Therefore, it is necessary to realize the combination of production and education, cultivate applied talents related to sports, promote physical and mental health, and check the impact of this training mode on emotional regulation. Subjects and Methods From the perspective of sports promoting physical and mental health, starting from the cultivation of sports application-oriented talents. Under the requirements of sports service-oriented physical and mental health talents, according to the function of colleges and universities to provide services for the society, combined with the interactive mode of foreign colleges and universities and local economic development, this paper puts forward the University oriented talent training mode of industry university research cooperation, so as to solve the bottleneck problem that the supply and demand sides of sports train physical and mental health application-oriented talents in terms of structure, quality and level. Through the correlation analysis of production and education mode, the data results show that through the investigation of the impact of emotional behavior, there is a significant positive correlation between psychological expectation and emotional regulation ability (P < 0.01), and there is a significant correlation between production and education mode, emotional coping, psychological elasticity and anxiety relevant. It has a significant positive correlation with anxiety, a significant positive correlation with emotion oriented coping, and a significant negative correlation with psychological elasticity; There was a significant negative correlation between emotional coping and psychological resilience; There was a significant negative correlation between psychological elasticity and anxiety. Results It is proposed that building the combination of industry and education and cultivating sports application-oriented talents can lay a solid foundation for people's physical and mental health. 1. “Wisconsin” - University oriented training path: University oriented, providing local people with intellectual and technical support for using sports to promote physical and mental health; 2. “Silicon Valley” - the cultivation path of the combination of industry, University and research: the combination of industry, University and research is formed. Universities and local economies promote each other to achieve mutual benefit and win-win results; 3. “Interactive University” - the cultivation path of symbiosis between colleges and local economy: clarify the idea of “serving local sports” in Colleges and universities. Make use of the human resources, intellectual support and scientific research achievements of sports to promote physical and mental health, so as to provide guarantee for the local realization of zero distance graduation and employment. Conclusion The combination of production, study and research of sports applied talents can not only advocate national fitness, enhance physical and mental health in the 21st century, form a healthy and civilized lifestyle, guide human resources with scientific fitness and heart health, meet the diversified sports needs of the masses, improve the training mechanism of sports service talents in Colleges and universities, and improve the demand-oriented training mode of sports talents, Comprehensively improve the quality of human resources on how to use sports to promote physical and mental health, and better serve the society. In short, we should carry out relevant combination of industry and education according to our own advantages and characteristics. Make clear the goal of motivation by example, and regularly hold activities such as successful model sharing, experience introduction and project display, so as to set a successful example for positive emotions, clarify the specific objectives of the activities, form a strong psychological momentum, stimulate internal potential and help the realization of positive behavior. We should strengthen professional guidance, give full play to the concentration of professionals, high intelligence, professional knowledge in business fields, and give full play to the advantages of talents and intelligence. We can organize experts and scholars to establish a professional bid winning guidance team, give full play to the business projects of experts and scholars in their respective fields, and carry out scientific research on relevant projects. Acknowledgements Supported by a project grant from department of education of Jilin province (Grant No.JJKH20190527SK).